2009
DOI: 10.1128/jcm.01425-08
|View full text |Cite
|
Sign up to set email alerts
|

Isopropyl Alcohol Compared with Isopropyl Alcohol plus Povidone-Iodine as Skin Preparation for Prevention of Blood Culture Contamination

Abstract: Despite a number of studies on the efficacies of antiseptics for the prevention of blood culture contamination, it still remains unclear which antiseptic should be used. Although the combination of povidone-iodine and isopropyl alcohol has been traditionally used in many institutions, the application of povidone-iodine needs extra time, and there is little evidence that this combination could have an additive effect in reducing contamination rates. To elucidate the additive efficacy of povidone-iodine, we comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 29 publications
2
32
0
Order By: Relevance
“…The overall blood culture contamination rate in this study, 4%, lies within the wide range (0.42% to 15.1%) reported previously for various settings (1,2,4,10,11,15,19,24,31,32,34,38) and is close to that of other ICU populations (5.5% [7]). The overall blood culture rate of detection of true pathogens is similarly consistent with those reported previously for other ICU patient series, 4.6% (7) to 12.8% (21).…”
Section: Discussionsupporting
confidence: 48%
“…The overall blood culture contamination rate in this study, 4%, lies within the wide range (0.42% to 15.1%) reported previously for various settings (1,2,4,10,11,15,19,24,31,32,34,38) and is close to that of other ICU populations (5.5% [7]). The overall blood culture rate of detection of true pathogens is similarly consistent with those reported previously for other ICU patient series, 4.6% (7) to 12.8% (21).…”
Section: Discussionsupporting
confidence: 48%
“…Therefore, we assume that use of a single application of 70% IPA is sufficient and clinically feasible for avoiding contamination when well‐trained residents obtain blood cultures. The present results are consistent with a previous prospective, non‐randomized study conducted in the adult population at the present medical center in 2009, which showed a lack of difference in the contamination rate between the IPA + PI group and the IPA group …”
Section: Discussionsupporting
confidence: 93%
“…). This change took place based on a prospective adult‐based study at the hospital in 2009 . In both periods, 2–3 sheets of IPA were used and rubbed firmly for the blood collection site.…”
Section: Methodsmentioning
confidence: 99%
“…92 Table 2 updates BCC outcomes as initially compiled by Trautner et al in 2002 68 and includes several additional trials. 70,[93][94][95][96][97][98][99][100][101][102][103] The most widely studied alcoholic CHG concentration is 2%, with most findings below the desirable BCC rate of 3%. Despite several limitations of the cited studies (eg, variations in the definition of contamination and personnel drawing BCs, potential confounding effect of multiple interventions, lack of compliance monitoring to established protocols), it would appear that solutions combining IPA and CHG are superior products in health care for many patient populations in a wide variety of settings, 50,104 providing effective bacterial kill and a rapid drying time of 30 seconds.…”
Section: Antisepsis Of Skinmentioning
confidence: 99%